Role of Big Data Analytics Capabilities and Entrepreneurial Orientation on Innovation Performance of Family-Owned Businesses: A Study of Pakistan’s Textile Industry - Amna Aslam; Asif Khurshid; Abdul Basit Rahil (Indus Journal of Social Sciences, 2025)
In this highly competitive and technological oriented world, organizational business practices have been changing day by day to emergence of new-fangled innovations, advanced technologies which includes artificial intelligence, big data analytics, cloud computing and business intelligence takes place in order to managing the businesses effectively and efficiently. However, they all are contributing in their own unique ways whereas big data analytics is the advanced method which is used for effective & timely decision making with help of advanced tool, software’s and techniques for managing and handling the businesses effectively (Sheng et al., 2019; Zeng & Khan, 2018). In organizations, the vital foundation in achieving a competitive advantage in order to survive and compete is sustainability which brings value in shifting the economic paradigm (Ferasso et al., 2020). It is found that BDAC improves the organizations overall performance which includes operational processes, enhance decision-making capabilities, minimize the cost as well as increases the quality of innovation (Benzidia, Bentahar, Husson & Makaoui, 2024). Moreover, by striving to improve coordination, build fruitful collaborations, raise awareness, and fortify institutional structures, Pakistan is moving closer to fulfilling its commitment to the 2030 Agenda. However, this research study will help to implement and sheds light based on resource-based theory on how BDAC can boost innovation strategy and performance of an organization. Innovation also occurs based on data-driven models for decision making, which enable businesses to create and design novel goods and services that may meet customer demands and reduce innovation-related risk (Ji, Yu, Tan, Kumar & Gupta., 2024). Data for this study was gathered from managers of family-owned businesses. 301 managers from family-owned textile companies made up the study's sample size, which was determined by employing the purposive sampling technique. Data for this study was gathered through questionnaires using a quantitative technique. PLS-SEM for quantitative data analysis was used to examine the data. Additionally, the results of this study show that big data analytics skills and an entrepreneurial mindset positively affect the firm's strategic innovation, which raises an organization's innovation performance. Technological transformation is significant because it improves economic business processes, which can have a favorable effect on emerging nations like Pakistan.